2016
DOI: 10.1007/s00705-016-2999-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phylogenetic analysis of a novel parvovirus isolated from chickens in Guangxi, China

Abstract: A previously unidentified chicken parvovirus (ChPV) strain, associated with runting-stunting syndrome (RSS), is now endemic among chickens in China. To explore the genetic diversity of ChPV strains, we determined the first complete genome sequence of a novel ChPV isolate (GX-CH-PV-7) identified in chickens in Guang Xi, China, and showed moderate genome sequence similarity to reference strains. Analysis showed that the viral genome sequence is 86.4 %-93.9 % identical to those of other ChPVs. Genetic and phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…The sequences of the NS gene obtained in the present study showed a high similarity with other ChPV sequences from other parts of the world, clustering with ChPV, and one sequence clustered with the Turkey Parvovirus (TuPV), but this result does not indicate that this sequence belongs to TuPV [ 28 ]. This result is in accordance with other studies in which some partial sequences of the ChPV NS gene cluster with the TuPV genome [ 28 ], which is useful for diagnosis but not for genetic classification for which the VP2 gene is much more suitable [ 28 , 35 , 36 ]. However, other studies should be done to determine which genotypes are currently circulating in poultry flocks in Brazil.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The sequences of the NS gene obtained in the present study showed a high similarity with other ChPV sequences from other parts of the world, clustering with ChPV, and one sequence clustered with the Turkey Parvovirus (TuPV), but this result does not indicate that this sequence belongs to TuPV [ 28 ]. This result is in accordance with other studies in which some partial sequences of the ChPV NS gene cluster with the TuPV genome [ 28 ], which is useful for diagnosis but not for genetic classification for which the VP2 gene is much more suitable [ 28 , 35 , 36 ]. However, other studies should be done to determine which genotypes are currently circulating in poultry flocks in Brazil.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were found in the present study in which apparently healthy chickens also showed high viral concentrations [ 22 ]. ChPV has been detected in chickens independently of zootechnical interest and in many regions around the world with high chicken production, such as Europe [ 10 , 17 , 18 ], China [ 35 ], South Korea [ 36 ], North America [ 8 , 37 , 38 ], Brazil [ 9 , 16 , 24 , 25 ], and Ecuador [ 26 , 38 ]; however, its presence remains unknown in the rest of South America. The present study also showed that the virus was detected at earlier and later ages in chickens, demonstrating that virus dissemination can occur at any time [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological investigations demonstrated wide distribution of parvoviruses in commercial chicken and turkey flocks in the United States and European countries including Hungary, Poland and Croatia Bidin et al, 2011;Domanska-Blicharz et al, 2012). Recent surveys indicated incidence of ChPV from Asia (South Korea and China), Brazil, Canada and United Kingdom (Fountain et al, 2011;Koo et al, 2013;Nuñez et al, 2015;Devaney et al, 2016;Feng et al, 2016). The details of prevalence of aveparvovirus with their health status, reported from different countries, is given in Table 2.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…Parvoviruses are associated with disease in a variety of host species, ranging from canines [49], livestock [50][51][52][53], rodents [36], and humans [54]. Reptile parvoviruses were identified in several snake species (snake adeno-associated virus) [11,[55][56][57][58][59] , some lizard species [11] including bearded dragons [11,12].…”
Section: Discussionmentioning
confidence: 99%